Analysis of Job Stress and Burnout to Organizational Citizenship Behavior of Officers with Intervening Variables Commitment Organization at dr. Nur's Clinic, Cimahi City - Jessica Yosalinata; Rian Andriani; Yen Efawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
As a healthcare institution with a high workload, it is important to understand the factors that influence staff extra-role behavior in order to improve overall service performance. This study aims to analyze the influence of job stress and burnout on Organizational Citizenship Behavior (OCB) with organizational commitment as an intervening variable at Dr. Nur Clinic, Cimahi City. This study uses a quantitative approach with a cross-sectional design, involving 139 respondents who have worked for more than six months. Data were collected through a questionnaire measuring work stress levels (based on Osipow's dimensions), burnout (based on Maslach's three components), organizational commitment (affective, normative, continuance), and OCB (altruism, responsibility, courtesy, sportsmanship, and civic virtue). Data analysis was conducted using multiple regression tests, path analysis, and mediation tests using SPSS version 29. The results of the study indicate that work stress and burnout each have a significant negative effect on organizational commitment and OCB. Organizational commitment was found to mediate the relationship between stress and burnout on OCB, with a greater mediating effect for stress than for burnout. Additionally, there is a serial effect of stress and burnout on OCB through reduced organizational commitment, highlighting the importance of a holistic approach in managing employee well-being. These findings indicate that enhancing organizational commitment as a form of employees' psychological attachment plays a crucial role in promoting OCB and mitigating the negative impacts of work-related stress.